The Role of Tai Meuay Tales in Explaining Animals - SOUTTHIXAY, souksada; SENGSOULIN, Bounleuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This article analyzes the role of Tai Meuay tales in explaining the names, characteristics, and behaviors of animals, based on the theoretical framework of Siraporn Na Thalang. A total of 100 tales from Phonsi Village, Khamkert District, Bolikhamxay Province were collected, analyzed, and interpreted, with textual examples provided for support. The findings were also presented through content analysis. The study reveals that some tales explain the origins of animal names and physical characteristics—for example, the names of Pa Pak (carp) and Pa Nai Kham (golden tilapia), the striped-necked dove, the head of houseflies, the big-nosed pig, the tortoise shell, the striped tiger, buffaloes' lack of upper teeth, the twisted-neck dove, caterpillars carrying firewood, lazy bugs, bent-backed shrimp, and the origin of monkeys. Other tales focus on animal behaviors, including the cries of frogs and owls, the blood-feeding of bed bugs, the crocodile's open mouth, monkeys’ inability to enter water, ducks eating bran, pigs eating feces, dogs avoiding buffalo feces bugs, fish living in water, tortoises living on both land and water, crocodiles’ inability to climb trees, tigers’ fear of toads, enmity between cats and dogs, rivalry between grasshoppers and finches, and the refusal of squirrels and chipmunks to enter water.